Enhancing COVID-19 booster vaccination among the elderly through text message reminders - Yi-Cheng Lee; Bing-Hau Lee; Yi-Hsuan Lin; Bih-Ju Wu; Tzeng-Ji Chen; Wei-Ming Chen; Yu-Chun Chen (Human Vaccines & Immunotherapeutics, 2024)
The BOOST (Booster promotion for older outpatients using SMS text reminders) program at Taipei Veterans General Hospital assessed the effectiveness of text message reminders in enhancing COVID-19 booster vaccination rates among the elderly, guided by the Health Belief Model (HBM). Targeting patients aged 65 and above, eligible yet unvaccinated for a COVID-19 booster, this cohort study sent personalized reminders a week prior to their scheduled appointments between April 18, 2022, and May 12, 2022, acting as cues to action to enhance vaccination uptake by overcoming perceived barriers and raising awareness of benefits. Over 5 weeks, the study observed a 38% increase in vaccination rate among 3,500 eligible patients, markedly surpassing the concurrent national rate increase of 4% for the same demographic. The majority of vaccinations occurred within two weeks after the reminder, illustrating the effectiveness of the strategy. Cox regression analysis identified age and time since last vaccination as significant predictors of responsiveness, with those aged 65–74 and 75–84 showing higher uptake, particularly when reminders were sent within 4 months after the last dose. A single reminder proved to be effective. The findings of this study demonstrate the potential of SMS reminders to promote COVID-19 vaccination among the elderly through the strategic use of HBM principles, suggesting a feasible and effective approach to public health communication.